Re-fuelling the talent tank. A qualitative study of key deficiencies, future needs, and life-long learning needs of communication management professionals in Europe (Communication & Society, 2017)
This paper originates from the results of the EU financed project, ECOPSI, which advanced understanding about the professional competences of European public relations and communication managers. The paper focuses on deficiencies in competences that practitioners identify for themselves and on the needs for the future generation that will perform four professional roles: chief communication officer (CCO), crisis communication, social media, and internal communication. Questions to understand the roles and their future requirements were defined around: means for achievement of current competences to perform the role, competence gaps, specialized competences, and future needs. They were explored with qualitative methodology through 53 in depth interviews. The analysis of data shows that European professionals understand and evaluate their way of performing the practice through a complex framework of competences. The findings provide evidence of synergies in the understanding and interpretation of the four roles and there is common identification of on-going gaps and future needs, suggesting that public relations is a maturing discipline with an accumulated set of standards in Europe. The study also targets the capacity of intervention for advancing the profession to an approach of knowledge acquisition and supporting the previous academic consensus about the necessity of a body of knowledge and specialized skills for professionalization